Efficient Infrastructure Setup in East Tanjung Jabung: Survey and Budget Analysis - Tarmuji, Tarmuji; Abidin, Zaenal; Wandi, Wandi; Nisak, Sayida Khoiratun (Zabags International Journal of Engagement, 2024)
This study aims to analyze the infrastructure needs in East Tanjung Jabung and identify efficient budgeting strategies in meeting the needs of the community. With a mixed-methods approach, the survey was conducted to understand the community's infrastructure priorities, while the analysis of regional financial documents was used to evaluate the effectiveness of budget allocation. The results of the study show that road access, sanitation, and health facilities are the main needs, but budget limitations and uneven distribution hinder the fulfillment of these needs. The findings also show that the budget is still largely allocated to short-term projects that are less strategic in the long term. Based on these results, it is recommended that the government implement needs-based budgeting that focuses on priority areas and involves the community in the planning process. This approach allows for more efficient, effective, and sustainable infrastructure development, thereby reducing inequality and improving community welfare